Using experience to develop leadership talent : how organizations leverage on-the-job development - McCauley, Cynthia D. (Cynthia Denise), 1958-; McCall, Morgan W. (San Francisco, CA : Jossey-Bass, 2014)
"How organizations can effectively put experience at the center of the development processResearch increasingly and conclusively shows that effective leaders continue to learn, grow, and change throughout their careers and that a significant part of this development occurs through on-the-job experiences. Co-Published by the Society of Industrial and Organizational Psychology and sponsored by the Center for Creative Leadership, Using Experience to Develop Leadership Talent provides real-world strategies, best practices, lessons learned, and global perspectives on how organizations effectively use experience to develop talent. Provides an in-depth look at a variety of leader development initiatives that have taken up the challenge of putting experience at the center of the development process Written by senior practitioners who have implemented initiatives they write about Shares new development planning tools, systematic approaches to managing the assignments of high potentials, tools to educate managers on how to find assignments that meet their employee's development needs Includes online resources that allow employees to search for development opportunities Describing challenges and practices in multinational companies around the world, Using Experience to Develop Leadership Talent will serve as a focused guide to how organizations can use on-the-job development to reshape leader development practices that better integrate work and learning"--
Includes index.
Machine generated contents note: List of Figures, Tables, and Exhibits Foreword: Series Editor (Allen I. Kraut) Foreword: A Senior HR Executive Perspective (Moheet Nagrath) Foreword: A Senior Line Executive Perspective (Inge G. Thulin) Acknowledgements The Editors The Contributors Section I: Introduction Chapter 1: Experience-Driven Leadership Development: Surveying the Terrain (Morgan W. McCall, Jr. and Cynthia D. McCauley) Section II: Putting Experience at the Center of Talent Development Systems Chapter 2: Building Leadership Breadth at Eaton Corporation (Connie Wayne) Chapter 3: Developing a Pipeline of Internal Leadership Talent at 3M (Karen B. Paul, Cindy Johnson and Kathie Karls) Chapter 4: Developing Leaders at All Levels at Yum! Brands (J. Tim Galbraith and Jim Howard) Chapter 5: Experience-Based Development: Building a Foundation at Kelly Services (Brad Borland, Terry Hauer and Laura Ann Preston-Dayne) Chapter 6: Leading from Where You Are: Driving On-the-Job Development into the Whole Organization (Paul R. Yost) Section III: Designing Job Experiences for Leader Development Chapter 7: A Project-Based Approach to Developing High-Potential Talent in the Tata Group (Satish Pradhan, Radhakrishnan Nair and Asma Bagash) Chapter 8: Collaborative Leadership in the Intelligence Community: Joint Duty Program (Elizabeth B. Kolmstetter) Chapter 9: Advancing Strategic Work and Accelerating Leadership Talent at GlaxoSmithKline (Kim Lafferty and Steve Chapman) Chapter 10: Developing IBM Leaders through Socially Responsible Service Projects (Vicki Flaherty and Mathian Osicki) Chapter 11: Using Part-Time Assignments to Broaden the Senior Leadership Pipeline at Genentech (Nisha Advani) Chapter 12: An Indian Experience of Leader Development: The Fire of Experience and Krishna-Arjuna Coaching (P.V. Bhide, Meena Surie Wilson, Rajeev Kakkar and Dilep Misra) Chapter 13: Virtual Reality and Leadership Development (Randall W. Hill, Jr.) Section IV: Maximizing Learning from Experience Chapter 14: Formal Development Enhances Learning from Experience at Microsoft (Lori Homer) Chapter 15: Experience-Based First-Line Manager Development at HEINEKEN (Mary Mannion Plunkett and Dagmar Daubner) Chapter 16: Turning Experience into Expertise: The Everyday Learning Disciplines for Leaders (Jeffrey J. McHenry and D. Douglas McKenna) Chapter 17: Catalytic Converters: How Exceptional Bosses Develop Leaders (Morgan W. McCall, Jr. and Jeffrey J. McHenry) Section V: Conclusion Chapter 18: Putting Experience at the Heart of Leader Development: Concluding Thoughts (Cynthia D. McCauley and Morgan W. McCall, Jr.) Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Employees -- Training of; Career development; Leadership; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Career development; Employees -- Training of; Leadership; Electronic books; Electronic books